LINGUISTIC UNITS FORMING CAUSATIVE MEANING - Musaev Abish Abilkazievich (International Journal Of Literature And Languages, 2024)
The article deals with comparative study of linguistic units that express causative meaning in English and Karakalpak languages. It is noted that there are similarities and differences of causative structures that can be formed morphologically and syntactically. Moreover, some scholars’ views were stated and examples of causative verbs were taken from literary texts in order to reveal causative meaning used in the text. Due to the study, analytical form is used to express causative meaning in English while it is mostly formed morphologically in Karakalpak language.